Endoscopic submucosal dissection in low volume centres - A multi-center survey from South East Asia - Azmi, AN; Khor, CJL; Ho, KY; Pittayanon, R; Rerknimitr, R; Ratanachu-Ek, T; Koay, DSC; Koh, JC; Ho, SH; Mahadeva, S (Wiley-Blackwell, 2024)
Indexed by WOS